Implementasi Pendidikan Karakter Religius Di Ma Paradigma Palembang - Ibrahim Ibrahim; Sinta Anggreini; Martadila Martadila; Selli Selli; Muhammad Iqrom (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Religious character education has become a primary concern in efforts to cultivate a younger generation with strong morals and religious values. This research aims to examine the implementation of religious character education at MA Paradigma Palembang as an effort to shape religious personality in students. The research is qualitative with a descriptive approach. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data collection, data presentation, verification, and drawing conclusions. The research results indicate that the implementation of religious character education at MA Paradigma Palembang has involved several key components. Firstly, religious character education must be integrated into the school curriculum, both in religious subjects and other subjects. Secondly, the role of teachers is crucial and has been carried out by setting an example and providing guidance to students in developing religious attitudes and behaviors. Thirdly, a school environment that supports and encourages religious practices also influences the formation of students' religious character